Microbial shifts of faecal microbiota using enteral nutrition in vitro. (February 2021) - Modrackova, Nikol; Copova, Ivana; Stovicek, Adam; Makovska, Marie; Schierova, Dagmar; Mrazek, Jakub; Sabolova, Monika; Vlkova, Eva; Hradsky, Ondrej; Bronsky, Jiri; Nevoral, Jiri; Neuzil-Bunesova, Vera
Graphical abstract: Highlights: Enteral nutrition (EN) formulas contain variable nutrient and prebiotic compounds. Cultivable commensal bacteria of faecal microbiota are able to use EN formulas like growth media in vitro . Composition differences of EN formulas affecting individual microbial shift and metabolite profile after cultivation. Functional components should be personalised based on individual host microbiota. Abstract: Enteral nutrition (EN) formulas of polymeric type ordinarily have similar content of intact macronutrients but may vary in prebiotic saccharides and micronutrients. These components can play an important role in the intestinal microbiota modulation. The aim of this study was to investigate microbial changes of faecal samples after their in vitro anaerobic cultivation in four polymeric EN formulas using plate technique method, metabolite analysis, and microbiota profiling using 16S rRNA sequencing. Detected cultivable commensal groups (bifidobacteria, lactobacilli, Escherichia coli ) in faecal samples of donors were able to grow in EN formulas. However, their counts varied depending on the individual donor and the type of EN formula. Similar trend was found in detected metabolites such as acetate, lactate, and butyrate. Also, taxonomic composition and diversity of original and cultivated faecal microbiota of one individual on different EN formula indicate a possible effect of the prebiotics and micronutrients to modulate gut microbiota.